Spiritual and physical development during the adaptation period of young players - Kaipnazarov Polat Muratbayevich (Zien Journals, 2024)
This article describes the features of attracting young people to sports, the activities of athletes, the process of training young players and working with them.The selection of young players, the selection system and the further development of the football infrastructure, the factors of training the strength of young players are also highlighted. The article presents the structure of the technology of football application in the department of sports improvement of young football players.
Keywords: Physical education; structure; technology; young football players